Perfect traders, bad churchgoers? Death in the service of the French Royal African Company - (:unkn) unknown (My University, 2017)
In order to organise its business activities, the Royal Africa Company expatriates, from 1741 to 1793, a few hundred employees, from, in general, Provence in commercial establishments in Muslim territory, situated in the regency of Algiers essentially. While the international agreements concluded to allow these facilities and trade are silent on how to behave in the event of death, how do the officers in charge of the management of these counters manage the questions relating to burials?
Keywords: African Research